2014
DOI: 10.1039/c3dt52219a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic composite BiOCl–SrFe12O19: a novel p–n type heterojunction with enhanced photocatalytic activity

Abstract: The magnetic composite BiOCl-SrFe12O19, a novel p-n type heterojunction was synthesized by hydrolysis with a medium temperature sintering method. The microstructure and magnetic properties of the prepared material were characterized by FTIR, XRD, SEM, TEM, HRTEM, SAED, and VSM. The results showed the [001] facet of BiOCl with high photocatalytic activity was exposed in the BiOCl-SrFe12O19. The heterostructured BiOCl-SrFe12O19 had better magnetic properties, contributing to its reuse and improvement in photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…7) results confirm that we succeeded in synthesizing core/ shell style (SFO/Fe 3 O 4 ) nano-composite magnets. There have been other successful synthesis approaches to synthesize Sr or Ba hexaferrite/soft magnet composites, [27][28][29] although previous work targeted different applications rather than permanent magnets. Multi-step methods like the one presented here are well suited for synthesizing core/shell structures 14 that allow more control on the morphology and amount of individual phase (hard and soft) needed for producing coupled permanent magnets.…”
mentioning
confidence: 99%
“…7) results confirm that we succeeded in synthesizing core/ shell style (SFO/Fe 3 O 4 ) nano-composite magnets. There have been other successful synthesis approaches to synthesize Sr or Ba hexaferrite/soft magnet composites, [27][28][29] although previous work targeted different applications rather than permanent magnets. Multi-step methods like the one presented here are well suited for synthesizing core/shell structures 14 that allow more control on the morphology and amount of individual phase (hard and soft) needed for producing coupled permanent magnets.…”
mentioning
confidence: 99%
“…In addition, the first-order reaction rate equations are shown in Table 2, indicating that the photocatalytic process of MO decolorization conforms to first-order kinetics. 38,39 From Table 2, we find that the reaction rate constant decreased as the methyl orange concentration increased. As is well-know, physical interpretation of reaction rate constant is reaction rate of unit concentration (1 mol L -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…By means of FTIR spectroscopy, they recorded the sharpest absorption bands of pure BiOCl at 529, 524, 535 and 523 cm´1, respectively, and a weak peak at approximately 1650 cm´1 (Table 8). Chang et al (2014) and Xie et al (2014) [71,72] reported a broad, weak absorption at 3450 cm´1 (Table 8). Ye et al (2012) [69] and Bai et al (2014) [70] published IR spectrums up to 2000 cm´1 and documented a minor peak at 1395 cm´1 (Table 8).…”
Section: Biocl Naturally Occurringmentioning
confidence: 99%
“…The [69][70][71][72]. By means of FTIR spectroscopy, they recorded the sharpest absorption bands of pure BiOCl at 529, 524, 535 and 523 cm´1, respectively, and a weak peak at approximately 1650 cm´1 (Table 8).…”
Section: Biocl Naturally Occurringmentioning
confidence: 99%